An isotopic study of atmospheric lead in a megacity after phasing out of leaded gasoline. (January 2017) - Gioia, S.M.C.L.; Babinski, M.; Weiss, D.J.; Spiro, B.; Kerr, A.A.F.S.; Veríssimo, T.G.; Ruiz, I.; Prates, J.C.M.
Abstract: Atmospheric lead (Pb) concentrations in São Paulo city, Brazil, remain significant, despite the fact that leaded gasoline was phased out. The use of its isotope signature allows tracing emissions to the increasing number of cars, urban construction, and industrial emissions in this densely populated area. High-precision and accurate stable isotope ratio determinations using isotope dilution thermal ionization mass spectrometry (ID-TIMS) combined with particle induced X-ray emission (PIXE) and multivariate analysis were used to identify the main sources of lead present in São Paulo atmospheric particulates. Throughout a period of sixty days, aerosol samples were collected every 12 h during the summer of 2005 at the University of São Paulo (USP) and simultaneously during one week in an industrial area (Cubatão) and in two more remote areas (São Lourenço da Serra and Juquitiba). The data suggests that aerosols from São Paulo are mainly derived from vehicular exhaust (mostly gasoline) and traffic dust resuspension, with the admixture of industrial emissions, including cement. Lead isotopic compositions (expressed as 206 Pb/ 207 Pb ratios) measured in São Paulo aerosols range from 1.1491 to 1.2527 and are similar to those determined from tunnel dust, fuels, and vehicular exhaust; therefore, those are likely to be the main lead sources in the atmosphere of São Paulo. Vehicular traffic (fuel combustion, dust from vehicular components, and road dust) remains an important source of lead in the atmosphere. The maximum concentration occurring during the summer was 0.055 μg m −3 in fine particles, which is detrimental for human health and may lead to exceedances of the Air Quality Standard for lead of 0.15 μg m −3 (3-month average) during other seasons when the dispersion of pollutants is less favourable. Highlights: Air mass transport from eastern industrial area to São Paulo was identified. Pb concentration still is significant after phasing out leaded gasoline. Pb pollution is a serious consequence of having an intensely urbanized city. São Paulo city has a diverse number of atmospheric lead sources.